Leverage and risk-taking in a dynamic model - Tobias Berg; Florian Heider (Leibniz Institute for Financial Research SAFE, 2024)
This paper examines the dynamic relationship between firm leverage and risktaking. We embed the traditional agency problem of asset substitution within a multi-period model, revealing a U-shaped relationship between leverage and risktaking, evident in data from both the U.S. and Europe. Firms with medium leverage avoid risk to preserve the option of issuing safe debt in the future. This option is valuable because safe debt does not incur the expected cost of bankruptcy, anticipated by debt-holders due to future risk-taking incentives. Our model offers new insights on the interaction between companies' debt financing and their risk profiles.
Keywords: G3; G31; G32; G33; 330; leverage; risk-taking incentives; dynamic model